Kedudukan Permohonan Putusan Provisi Dalam Hak Uji Materi (Judicial Review) Pada Hukum Acara Mahkamah Konstitusi - Muhammad Helmi Fahrozi; Antonius Julio Parlindungan (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
The idea of establishing a Constitutional Court (MK) is one of the developments in modern legal and state thinking that emerged in the 20th century. After the New Order, the institutional structure of the state underwent changes, one of which was the formation of the Constitutional Court through the third amendment to the 1945 Constitution (UUD 1945). The establishment of the Constitutional Court as a special tribunal separate from the Supreme Court, which basically tests the compatibility of lower legal norms with higher legal norms. In addition to testing the conformity of legal norms, judicial review can also be carried out if the constitutional rights of the community are not fulfilled by the enactment of a law. If fulfilled, the decision of the Panel of Constitutional Justices can cancel or delete the contents of the products of the legislative body or the government. With a long process in judicial review, a provisional decision is needed as a temporary legal action to prevent or stop the enactment of a law being tested in order to avoid comprehensive legal consequences. The position of the petition for a provisional decision in judicial review is not clearly regulated in the statutory regulations, but in the practice of proceeding at the Constitutional Court in some cases, the result of the decision is in the form of a provisional decision. This study uses a normative juridical method by taking several approaches to the problem that contains aspects of the application for provisions in conducting judicial review of the material.Keywords: Testing, Law, Constitutional Court, Provisional Decisions AbstrakIde pembentukan Mahkamah Konstitusi (MK) merupakan salah satu perkembangan pemikiran hukum dan kenegaraan modern yang muncul di abad ke-20. Pasca Orde Baru, susunan kelembagaan negara mengalami perubahan salah satunya adalah pembentukan MK melalui amandemen Undang-Undang Dasar 1945 (UUD 1945) yang ketiga. Berdirinya MK sebagai special tribunal secara terpisah dari Mahkamah Agung, yang pada dasarnya menguji keserasian norma hukum yang lebih rendah dengan norma hukum yang lebih tinggi. Selain menguji keserasian norma hukum, pengujian undang-undang juga dapat dilakukan apabila hak konstitusional dari masyarakat tidak terpenuhi dengan berlakunya suatu undang-undang. Apabila terpenuhi, putusan Majelis Hakim Konstitusi dapat membatalkan atau menghapus isi dari produk badan legislasi atau pemerintah. Dengan proses yang panjang dalam pengujian undang-undang, dibutuhkan suatu putusan provisi sebagai tindakan hukum sementara guna mencegah atau menghentikan terlebih dahulu pemberlakuan suatu undang-undang yang sedang diuji guna menghindari akibat hukum yang menyeluruh. Kedudukan permohonan putusan provisi dalam pengujian undang-undang tidak diatur secara jelas dalam peraturan perundang-undangan namun dalam praktik beracara di MK pada beberapa kasus, hasil putusan berupa putusan provisi. Penelitian ini menggunakan metode yuridis normatif dengan melakukan beberapa pendekatan masalah yang terdapat aspek permohonan provisi dalam melakukan pengujian materi undang-undang.Kata Kunci: Pengujian, Undang-Undang, Mahkamah Konstitusi, Putusan Provisi